Absenteísmo por motivo de doença dos servidores técnico-administrativos da Universidade Federal de Mato Grosso Do Sul (UFMS) - Brunhera, Eliane Cristina (2022)
Absenteeism is related to the workers' absence from their work-related activities, causing negative impacts on the productivity of institutions and the profitability of organizations. Objective: Our main objective was to identify the causes of absenteeism motivated by illnesses through the analysis of medical certificates filed by technical-administrative employees of the Federal University of Mato Grosso do Sul (UFMS, Brazil). As specific objectives: a) to investigate the incidence of absenteeism motivated by illness, identifying them according to the International Classification of Diseases - ICD; b) map the absenteeism rates according to categories and place of work of civil servants. Methodology: This is a cross-sectional, retrospective, epidemiological, and descriptive study, obtained through secondary data and a quantitative analysis. We searched through the institutional archives, from which we extracted data from medical certificates filed by employees in a five-year time frame (2014 to 2018), subsequently organized in software Microsoft Excel 2016. The resulting calculations were analyzed to identify the main causes of sick leave and the diseases that had a causal link with the job, epidemiologically related to the International Classification of Diseases (ICD) code. Results: 7,854 medical certificates were found, which means a 0.92 Frequency Index (FI) and a loss of 111,223 working days, which represented a rate of 13.72 Severity Index (SI) and a Percentage of Lost Time (PLT) of 3.72%. The main causes of sick leaves were: mental and behavioral disorders (MBD), with 1,365 medical certificates, generating 41,200 lost work days, and musculoskeletal diseases (MSD), with 1,653 medical certificates and a loss of 25,414 working days. As for the professional categories, two stood out with the highest number of medical certificates: mid-level and intermediate-level civil servants, who had 2,913 and 2,689 certificates, causing 45,548 and 36,626 absences, respectively. The unit with the highest number of certificates and absences was the Hospital University – HUMAP, with 4,680 medical certificates (62.37%) and 61,328 lost working days (55.59%). Conclusion: The results presented confirm that absenteeism due to sick leave are episodes that occur frequently in the institution, impacting its productivity and the quality of life of its employees. Given this fact, it is necessary to adopt preventive and curative measures to reduce the absence due to illness of these professionals, as well as to increase their level of satisfaction with work, aiming to reduce absenteeism.